Cervical Endocrine Surgery With a Novel Opioid-Limited Perioperative Protocol. Issue 3 (March 2023) - Boudiab, Elizabeth M.; Lapkus, Morta; Reilly, Jordan; Studzinski, Diane; Czako, Peter; Asbahi, Moumen; Schostak, Michael; Schmidt, Carol; Nagar, Sapna
Background: Recent studies have demonstrated that patients undergoing cervical endocrine surgery could be comfortably discharged with minimal opioid analgesia. However, no study to date has examined the efficacy of limiting administration of opioids intraoperatively. We have developed a novel protocol for patients undergoing cervical endocrine surgery that eliminates perioperative opioids. We sought to determine the efficacy of this protocol and its impact on opioid use at discharge. Methods: We conducted a prospective opt-in opioid-limited surgery program study to opioid-naive patients scheduled for cervical endocrine surgery beginning in August 2019. Postoperatively, nonopioid analgesia was encouraged, but patients were also given a low dose prescription for opioids at discharge. Patients were then matched with 2 retrospective control groups, patients from 2014-2016 and 2017-2018, in order to account for increased public awareness of opioid-prescribing patterns. Primary end points included perioperative opioid use. Secondary end points included postoperative pain scores and complications. Results: 218 patients underwent cervical endocrine surgery with our opioid-limited protocol between August 2019 and February 2020. Nine patients received opioids intraoperatively (4%) and 109 (50%) filled their opioid prescriptions at discharge. Compared to retrospective control groups, the average oral morphine equivalents (OME) administered intraoperatively and prescribed postoperatively were significantly lower ( P < .0001). Pain scores and complication rates were similar in all groups ( P = .7247). Discussion: Our novel opioid-limited surgery protocol used in conjunction with preoperative counseling is an effective approach for pain control in patients undergoing cervical endocrine surgery and limits opioid exposure throughout the perioperative period.